Detection of HPV-16 L1 antigen using MoS2 nanosheets and amine-functionalized copper doped carbon dots - Rajmohan Swetha; Karutha Pandian Divya; Lakshmi Devi A; T.G. Satheesh Babu (Sensors and Actuators Reports)
HPV-16L1 is one of the important biomarkers for chronic cervical cancer. The present work deals with the development of a label-free electrochemical immunosensor by modification of electrode surface using 2D MoS2 nanosheets and amine functionalized copper doped carbon dots (f-CuCD). The copper doped carbon dot with high surface area 2D material like MoS2 provides a stable platform for the immobilization of antibody which aids in the sensor performance. The use of MoS2/f-CuCD is the highlight of this work through which effective anti-HPV immobilization on the surface is achieved. Electrochemical impedance spectroscopy (EIS) was used to analyse the response of different concentrations of HPV-16L1 on the modified screen printed carbon electrode (SPCE). On increasing the concentration of HPV-16L1, the RCT value gradually increased and the peak current decreased due to the low conductivity of the protein molecule. The developed immunosensor was found to detect wide concentration ranges of 0.01–100 ng/µL with a low detection limit of 8.30 pg/µL for HPV-16L1. Spiked human serum samples were also analysed. It also proves to be a sensitive, selective, stable and feasible tool for the determination of HPV-16L1.